Determination of Lactones in Wines by Headspace Solid-Phase Microextraction and Gas Chromatography Coupled with Mass Spectrometry - S. J. Pérez-Olivero; M. L. Pérez-Pont; J. E. Conde; J. P. Pérez-Trujillo (Journal of Analytical Methods in Chemistry)
Application of headspace solid-phase microextraction (HS-SPME) coupled with high-resolution gas chromatographic (HRGC) analysis was studied for determining lactones in wines. Six different SPME fibers were tested, and the influence of different factors such as temperature and time of desorption, ionic strength, time of extraction, content of sugar, ethanol, tannins and anthocyanins, and pH and influence of SO2 were studied. The proposed HS-SPME-GC method is an appropriate technique for the quantitative analysis of γ-butyrolactone, γ-hexalactone, trans-whiskey lactone, γ-octalactone, cis-whiskey lactone, γ-nonalactone, γ-decalactone, δ-decalactone, and γ-undecalactone in wines. Method reproducibility and repeatability ranged between 0.6 and 5.2% for all compounds. Detection limit for γ-butyrolactone was 0.17 mg/L and a few μg/L for the rest of the compounds. The optimized method has been applied to several wine samples.